Peran Strategi Hybrid Learning: Solusi Atas Krisis Efektivitas Pembelajaran Fiqih Tradisional di Pesantren Era Digital - Siti Patimah; Ahmad Fauzi Hasibuan; Neni Neni (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study discusses the relevance and role of hybrid learning strategies as a conceptual solution to the crisis of effectiveness in traditional fiqh learning in Islamic boarding schools in the digital age. The background of this study stems from the problem of declining efficiency and interactivity of classical learning methods such as sorogan and bandongan amid technological developments that demand pedagogical innovation. This study aims to analyze theoretically how the integration of traditional pesantren values and modern learning approaches can be applied without eliminating spiritual identity and scientific sanad. The method used is library research with a descriptive-analytical approach through a review of the latest scientific literature on Islamic education and hybrid learning. The results show that a hybrid learning model based on synchronous and asynchronous approaches can increase flexibility, effectiveness, and student participation in the learning process, while maintaining personal relationships with teachers. The theoretical implications enrich the concept of integrating Islamic education and technology, while the practical implications offer an adaptive curriculum model for Islamic boarding schools to respond to the challenges of the digital age without abandoning Islamic values.